A comparative analysis of retracted papers in Health Sciences from China and India. (2nd October 2020) - Palla, Ishfaq Ahmad; Singson, Mangkhollen; Thiyagarajan, S.
ABSTRACT: Academics are expected to publish their research work. Hence, during the past few years, the scientific community has witnessed an ever-increasing growth and output in scientific papers. However, a large number of authors have violated ethical norms of research leading to retractions of their research works as well. The article focuses on the scientific fraud emanating from China and India in Health Sciences for a period of three years i.e. 2015 to 2018. The present data were extracted from http://retractiondatabase.org/using a search filter term "Research Articles OR Articles in Press" on the subject category of Health Sciences (HSC). A total of 318 retracted papers were retrieved and the result of the study indicated that majority (268 items) of the retracted papers in Health Science originated from China, whereas just 50 retracted papers originated from India as on 21-02-2019. While analyzing the data, 26 redundant articles from China have been removed that received retraction notices. Further, the results of the study suggest that there are several factors associated with retraction of scientific papers, which include unreliable results, duplication of results, plagiarism, forged authorship, error in the text, error in data and so on.